THE POETICS OF RESISTANCE: MIRROR OF SOCIETY AND SOCIAL FUNCTIONS IN MAHMUD DARWISH’S QASIDAT AL-ARDH WITHIN IAN WATT’S SOCIOLOGY OF LITERATURE - Abdinda Firdausi Nuzula; Ma'rifatul Munjiah (Bahasa dan Sastra Arab, Fakultas Adab dan Humaniora, UIN Sunan Gunung Djati, 2025)
This study examines Mahmud Darwish’s poem “Qasidatu al-Ardh” (“The Poem of the Land”) through the lens of Ian Watt’s sociology of literature to understand how the text reflects and functions within the socio-political realities of Palestine. The study aims to (1) describe how the poem mirrors the social and political conditions of Palestinian life under occupation, (2) reveal the social values, nationalism, and ideological resistance expressed in the poem, and (3) explain the poem’s social functions as a medium of critique, collective consciousness, and ideological struggle. Using a qualitative-descriptive method, the analysis focuses on close reading of the Arabic text supported by secondary sources on Darwish, Palestinian history, and sociological literary theory. The findings show that Darwish constructs a poetic landscape in which land, identity, memory, and the body become symbolic sites of conflict and resistance. These results demonstrate that poetry, especially within contexts of oppression, serves as both a mirror and an agent of social transformation.